Two‐dimensional echocardiographic right ventricle measurements adjusted to body mass index and surface area in a normal population. Issue 4 (14th November 2016) - Eslami, Masood; Larti, Farnoush; Larry, Mehrdad; Molaee, Parisa; Badkoobeh, Roya Sattarzadeh; Tavoosi, Anahita; Safari, Saeed; Parsa, Amir Farhang Zand
ABSTRACT: Background: To determine reference echocardiographic values in a normal population and assess their correlation with body mass index (BMI) and body surface area. Methods: An expert cardiologist performed two‐dimensional echocardiography with triplicate right ventricle (RV) size measurements in 80 subjects with normal heart condition. Results were correlated with anthropometric data. Results: Base‐to‐apex length in four‐chamber view (RVD3) and above‐pulmonic valve in short‐axis view in males, as well as mid‐RV diameter in standard four‐chamber view (RVD), basal RV diameter, and mid RV diameter in RV‐focused four‐chamber view in females, were significantly correlated with BMI. All RV variables were significantly correlated with BMI in 20–30‐year‐old subjects. All RV variables except RVD3 and above‐aortic valve in short‐axis view (proximal) were significantly correlated with BMI in 35–55‐year‐old subjects. All RV parameters were significantly correlated with body surface area, except for RVD and in 20–35‐year‐old subjects. Conclusions: RV echocardiographic values must be adjusted to anthropometric characteristics for proper diagnosis and management of cardiac disorders. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :204–210, 2017;